Excitation functions of (d,x) nuclear reactions on natural titanium up to 24 MeV - Khandaker, Mayeen Uddin; Otuka, N.; Haba, H.; Kanaya, J. (Elsevier, 2013)
Excitation functions of the Ti-nat(d,x)V-48 and Ti-nat(d,x)Sc-43,Sc-44m,Sc-44g,Sc-46,Sc-47,Sc-48 nuclear reactions were measured up to a 24-MeV deuteron energy by using a stacked-foil activation technique combined with gamma-ray spectrometry with a high-purity germanium detector at the AVF cyclotron of the RIKEN RI Beam Factory, Wako, Japan. An overall good agreement is found between the measured cross-sections and the literature ones, whereas partial agreements are obtained for the theoretical calculations based on the TALYS code. Physical thick target yields, i.e., induced radioactivities per unit fluence of the 24-MeV deuteron were also deduced, and they were compared with the directly measured ones in the literature. The present results will have an important role in enrichment of the literature database of the deuteron-induced reactions on natural titanium leading to various applications. (c) 2012 Elsevier B.V. All rights reserved.